Effects of crop rotation, green manure, and nitrogen fertilizer on the bean yield - Arf, Orivaldo; Silva, Luiza Salustiano da; Buzetti, Salatiér; Alves, Marlene Cristina; Sá, Marco Eustáquio de; Rodrigues, Ricardo Antonio ferreira; Hernandez, Fernando Braz Tangerino (Pesquisa Agropecuaria Brasileira, 1999)
The present work was carried out at Selvíria, MS, Brazil, with the objective of evaluating the effects of velvetbean, lab-lab and corn crop residues on the development and yield of winter bean (Phaseolus vulgaris L.) crops. The experimental design utilized was a randomized blocks obtained through an arrangement between the incorporation of different organic residues, with and without nitrogen supply in the bean crop. Grain yield was higher when velvetbean was incorporated in rotation with corn crop residues. The best yield was obtained in the treatments: velvetbean incorporation, lab-lab and corn + velvetbean sowed 100 days after corn sowing. Application of 45 kg ha-1 of N fertilizer (urea) increased the yield of winter bean crops in 17,8%.